Animals as representations of female domestic roles in selected fables from the Philippines and South Africa - Genevieve Jorolan Quintero; Connie Makgabo (University of Johannesburg, 2020)
South Africa and the Philippines are home to a number of indigenous groups whose cultures and traditions have not been tainted by centuries of colonization. This paper compares the pre-colonial literature of cultural communities in two countries, where one is part of a continent (South Africa) while the other is an archipelago (the Philippines). Despite the differences in their geographical features, the two countries share common experiences: 1) colonized by European powers; 2) have a significant number of indigenous communities; 3) a treasury of surviving folk literature. Published African and Philippine folktales reveal recurring images and elements. One of these is the use of animals as characters, performing domestic tasks in households, and representing gender roles. This paper compares how animal characters portray feminine characteristics and domestic roles in selected fables from South Africa and the Philippines, specifically on the commonalities in the roles of the female characters. The research highlights the relevance of recording and publishing of folk literature, and the subsequent integration and teaching thereof within basic and higher education curricula. Key words: Indigenous, Cultural communities, fables, folk literature, Philippine folk tales, South African folk tales How to cite this article: Quintero, G.J. & Makgabo, C. 2020. Animals as Representations of Female Domestic Roles in selected fables from the Philippines and South Africa. Scholarship of Teaching and Learning in the South. v. 4, n. 1, p. 37-50. April 2020. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=121 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/